Lymphoplasmapheresis versus plasma exchange in severe myasthenia gravis: a retrospective cohort study - Duan, Weiwei; Jiang, Fei; Cai, Haobing; Li, Bijuan; Ouyang, Song; Yin, Weifan; Zeng, Qiuming; Yang, Huan (Frontiers in Neurology, 2023)
Background: Lymphoplasmapheresis (LPE) is a new therapy developed on the basis of traditional plasma exchange (PE) in combination with leukapheresis. Currently, it remains unclear whether PE and LPE show differences in efficacy for severe MG. Methods: A retrospective analysis was conducted on 198 MG patients, 75 in the PE group and 123 in the LPE group. Propensity score matching (PSM) was applied for the balance of confounders between the two groups. Results: In this study cohort, the safety profile of LPE and PE was good. Based on PSM, 62 patients treated with LPE and 62 patients treated with PE were entered into a comparative efficacy analysis. In the PE group, patients underwent a total of 232 replacements, with a mean of 3.74. PE significantly improved the patients' QMGS performance, with the mean QMGS decreasing from 22.98 ± 4.03 points at baseline to 18.34 ± 5.03 points after treatment (p < 0.001), and the treatment response rate was 67.7%. In the LPE group, patients received a total of 117 replacements, with a mean of 1.89. The patients' mean QMGS was 23.19 ± 4.11 points at baseline and was 16.94 ± 5.78 points after treatment (p < 0.001). The improvement in QMGS was more significant in patients treated with LPE compared to the PE group (p = 0.039). The treatment response rate in the LPE group was 79%, which was not significantly different compared to the PE group (p = 0.16). The LEP group had a shorter mean length of stay compared to the PE group (10.86 ± 3.96 vs. 12.14 ± 4.14 days, p = 0.13 ). During the 2-month follow-up period, LPE may be associated with better functional outcomes for patients, with lower QMG score and relapse rate. Compared to PE, LPE was superior in the reduction of AChR-Ab titer. Conclusions: In severe MG, LPE may be a more preferred treatment option than PE. It achieves treatment outcomes that are not inferior to or even better than PE with fewer replacements. This study provides further evidence to support the application of LPE as a new treatment option for MG.